Challenges and Opportunities of Developing an ESP University Course without a Textbook – a multiple case study - ROMAGNUOLO, Anna (Advances in Social Sciences Research Journal, 2020)
The growing demand for ESP courses, due not only to the use of English as a lingua franca in a globalized professional world but also to the relatively recent requirements of “internationalized” university degrees, has made the teaching of English for Special Purposes, with the areas and the language teaching approaches (EOP, EAP, EVP) it has come to include, increasingly reliant on the use of specialized EFL textbooks. However, the ESP books available in the market still might not cover all the non-linguistic specialized university disciplines, or they might be too costly and time-consuming for short, elective, and pass/fail EFL courses worth few ECTS credits. This paper will report on the author’s experience of teaching a University Business Communication course without the use of textbooks, and with significant resort to online free educational resources and “non-desktop” technologies, materials and tools, which have also been exploited to involve students in the preparation of flipped lessons and the creation of their own educational material. The course-specific features and students’ outcomes, especially in terms of competence and skill development, will be described with a brief analysis of the pros and cons of transforming a formal educational setting in an informal language learning experience.